Long-Term Outcomes of Elderly Brain Arteriovenous Malformations After Different Management Modalities: A Multicenter Retrospective Study - Chen, Yu; Yan, Debin; Li, Zhipeng; Ma, Li; Zhao, Yahui; Wang, Hao; Ye, Xun; Meng, Xiangyu; Jin, Hengwei; Li, Youxiang; Gao, Dezhi; Sun, Shibin; et al. (Frontiers in Aging Neuroscience, 2021)
Background: More and more elderly patients are being diagnosed with arteriovenous malformation (AVM) in this global aging society, while the treatment strategy remains controversial among these aging population. This study aimed to clarify the long-term outcomes of elderly AVMs after different management modalities. Methods: The authors retrospectively reviewed 71 elderly AVMs (>60 years) in two tertiary neurosurgery centers between 2011 and 2019. Patients were divided into four groups: conservation, microsurgery, embolization, and stereotactic radiosurgery (SRS). The perioperative complications, short-term and long-term neurological outcomes, obliteration rates, annualized rupture risk, and mortality rates were compared among different management modalities in the ruptured and unruptured subgroups. Kaplan-Meier survival analysis was employed to compare the death-free survival rates among different management modalities. Logistic regression analyses were conducted to calculate the odds ratios (ORs) and 95% confidence intervals (CI) for predictors of long-term unfavorable outcomes (mRS>2). Results: A total of 71 elderly AVMs were followed up for an average of 4.2±2.3 years. Fifty-four (76.1%) presented with hemorrhage, and the preoperative annualized rupture risk was 9.4%. Among these patients, 21 cases (29.6%) received conservative treatment, 30 (42.3%) underwent microsurgical resection, 13 (18.3%) received embolization, and 7 (9.9%) underwent SRS. In the prognostic analyses, the short-term and long-term neurological outcomes were similar between conservation and intervention both in the ruptured and unruptured subgroups (ruptured: p=0.096, p=0.904, respectively; unruptured: p=0.568, p=0.306, respectively). In the ruptured subgroup, the intervention cannot reduce long-term mortality (p=0.654) despite the significant reduction of subsequent hemorrhage than conservation (p=0.014), and the main cause of death in the intervention group was treatment-related complications (5 of 7, 71.4%). In the logistic regression analysis, higher admission mRS score (OR 3.070, 95% CI 1.559-6.043, p=0.001) was the independent predictor of long-term unfavorable outcomes (mRS>2) in the intervention group, while complete obliteration (OR 0.146, 95% CI 0.026-0.828, p=0.030) was the protective factor. Conclusions: The long-term outcomes of elderly AVMs after different management modalities were similar. Intervention for unruptured elderly AVMs was not recommended. For those ruptured, we should carefully weigh the risk of subsequent hemorrhage and treatment-related complications. Besides, complete obliteration should be pursued once the intervention was initiated.